Shoot Emergence, Leaf Expansion, and Corm Growth in Amorphophallus muelleri Blume Treated with Hydropriming and Shading - Benyamin Lakitan; Dora Fatma Nurshanti; Merry Hasmeda; Ferlinahayati Ferlinahayati (Faculty of Agriculture University of Brawijaya in collaboration with PERAGI, 2023)
A bulbil, as planting material, is difficult to stimulate to grow in a dormant state. This study examines the hydropriming effect on shoot emergence and the shading treatments on leaf and cormel growth during the vegetative stage. The priming was carried out by soaking the bulbils in distilled water for 0, 3, 6, 12, and 24 hours and the shading treatments at 0, 40, and 80 percent. The results show that the imbibition occurred immediately during the first 3 hours and continued to increase up to 24 hours. The bulbil re-drying process reached the pre-treatment water content in less than three days. Significantly the earlier emergence was observed in the plants exposed to the 80% shading. The petiole sheath breakup was not affected by the hydropriming and shading. The konjac planted in the shading treatment produced more sprouts, longer but slender petioles, larger but thinner leaves, and larger cormel size. The differences in fresh and dry weight were more related to tuber moisture content than the direct effect of the shading treatment. The SPAD value of konjac leaves immediately increased within a few days after the application of the NPK fertilizer and consistently lasted for four weeks.